Suatu Penelitian Mixed Methodelogy tentang Praktik Pendidikan Multikultural dan Sikap Iffah dalam Instruksi Aqidah Akhlak terhadap hasil belajar peserta didik: Kerangka Kerja Deliberasi STEAM Terintegrasi - Safiuddin, Safiuddin (CV. ULIL ALBAB CORP, 2025)
This study aims to examine the practices of multicultural education and the attitude of iffah in Aqeedah Akhlak instruction and its impact on students' learning outcomes at SMAN 03 Jakarta, utilizing a mixed methodology approach. The research integrates a deliberative STEAM framework (Science, Technology, Engineering, Arts, and Mathematics) within the context of Aqeedah Akhlak education, which emphasizes multicultural values and the attitude of iffah. A quantitative method is used to measure students' learning outcomes, while a qualitative approach focuses on analyzing the learning process, teacher-student interactions, and students' perceptions of the values applied. The findings reveal that the implementation of multicultural education combined with iffah attitudes in Aqeedah Akhlak instruction enhances students' learning outcomes, both cognitively and affectively. Furthermore, the integration of the deliberative STEAM framework proves effective in creating a more inclusive, participatory, and character-development-oriented learning environment. This research provides significant contributions to the development of educational models that accommodate cultural diversity and moral values in teaching.